TRANSFORMING COMMUNITY-BASED MADRASAS IN THE DIGITAL ERA - M. Amin Hasan; Hanun Asrohah; Keith Thong (STAI Ma'had Aly Al-Hikam Malang, 2026)
Madrasah transformation is a long-term process requiring collective support from various stakeholders as essential social capital. Active community involvement is a key strategy for sustainable reform. This study aims to analyze the influence of community participation levels on the scale of organizational and digital transformation within madrasahs to ensure they thrive in the Society 5.0 era. The methodology employs Participatory Action Research (PAR) using a multi-case study design across four madrasahs. Findings indicate that community participation can be categorized into four levels: informing, involving, participating, and leading. The depth of this support determines the scale of organizational transformation at micro, institutional, and macro levels. Furthermore, the level of community engagement correlates directly with technological maturity, distinguishing digital transformation stages into predigital, digitally mature, and post-digital transformation. The primary findings reveal that higher levels of community participation are strongly linked to accelerated organizational and digital shifts. This demonstrates that community synergy serves as the main driver in creating educational institutions that are adaptive to the integration of technology and human values in the future. Keywords: Community Engagement; Organizational Transformation; Digital Transformation. Abstrak Transformasi madrasah merupakan proses panjang yang membutuhkan dukungan kolektif dari berbagai pemangku kepentingan sebagai modal sosial utama. Keterlibatan aktif komunitas secara keseluruhan merupakan strategi kunci untuk reformasi berkelanjutan. Penelitian ini bertujuan untuk menganalisis pengaruh tingkat partisipasi masyarakat terhadap skala transformasi organisasi dan digital madrasah agar mampu berkembang di era Society 5.0. Metode yang digunakan adalah Participatory Action Research dengan desain studi multi-kasus pada empat madrasah. Hasil penelitian menunjukkan bahwa partisipasi masyarakat dikategorikan menjadi empat tingkatan: memberi informasi, melibatkan, berpartisipasi, dan memimpin. Tingkat dukungan tersebut menentukan skala transformasi organisasi pada level mikro, institusional, dan makro. Selain itu, kedalaman keterlibatan masyarakat berkorelasi langsung dengan kematangan teknologi, yang membedakan tahapan transformasi digital menjadi: pra-digital, digital matang, dan pasca-transformasi digital. Temuan utama mengungkapkan bahwa semakin tinggi tingkat partisipasi masyarakat, semakin kuat akselerasi transformasi organisasi dan digital di madrasah. Hal ini membuktikan bahwa sinergi komunitas adalah penggerak utama dalam mewujudkan institusi pendidikan yang adaptif terhadap integrasi teknologi dan nilai kemanusiaan di masa depan. Kata kunci: Keterlibatan Komunitas; Transformasi Organisasi; Transformasi Digital.